2011
DOI: 10.1093/ejo/cjr103
|View full text |Cite
|
Sign up to set email alerts
|

Load-deflection characteristics of superelastic and thermal nickel-titanium wires

Abstract: The aim of this study was to investigate the mechanical properties of superelastic and thermal nickel-titanium (NiTi) archwires for correct selection of orthodontic wires. Seven different NiTi wires of two different sizes (0.014 and 0.016 inches), commonly used during the alignment phase, were tested. A three-point bending test was carried out to evaluate the load-deflection characteristics. The archwires were subjected to bending at a constant temperature of 37°C and deflections of 2 and 4 mm. Analysis of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 25 publications
1
21
0
6
Order By: Relevance
“…Despite there is not a clear statement of the optimal force delivered to ensure an efficient orthodontic movement 13 , the interval of different lots described in the present work (104.8-161.1g = 102.7-157.8cN) is a little higher but still in accordance with literature results described above (60-239g = 58.8-234.2cN). The difference should be credited to divergences in the deflection maximum value, crosshead speed and span, which did not observe the recommendation of ISO 15841 or due to differences in the material behavior provided by different manufacturers and commercial available lots.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Despite there is not a clear statement of the optimal force delivered to ensure an efficient orthodontic movement 13 , the interval of different lots described in the present work (104.8-161.1g = 102.7-157.8cN) is a little higher but still in accordance with literature results described above (60-239g = 58.8-234.2cN). The difference should be credited to divergences in the deflection maximum value, crosshead speed and span, which did not observe the recommendation of ISO 15841 or due to differences in the material behavior provided by different manufacturers and commercial available lots.…”
Section: Discussionsupporting
confidence: 91%
“…Herein the force delivery during unloading, comparing the force considered suitable for clinical purposes described in orthodontic journals, Gatto et al 13 showed values between 60-100g when comparing different manufacturers, Bartzela et al 14 presented an interval between 139-239g and Lombardo et al 15 disclosed values between 78.4-109.6g [13][14][15] . All the authors tested different manufacturers of superelastic orthodontic .014'archwires, with exception of Bartzela et al who tested a .016'round wire.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Portanto, é de maior interesse clínico conhecer as forças liberadas pelo teste de descarga do que as forças liberadas pelo teste de carga (CHEN;ZHI;ARVYSTAS, 1992;FISCHER-BRANDIES et al, 2003;MURAVIEV;OSPANOVA;SHLYAKHOVA, 2001;WATERS, 1992b;YONEYAMA et al, 1992), uma vez que a descarga representa as forças que promovem a movimentação dentária durante o tratamento ortodôntico (ANDREASEN; HEILMAN;KRELL, 1985;BARTZELA;WICHELHAUS, 2007;WARAM, 2007;BURSTONE;QIN;MORTON, 1985;TAVERNIER;JORDAN, 2005;GATTO et al, 2013;KAPILA et al, 1991;LIAW et al, 2007;LOMBARDO et al, 2012;MURAVIEV;OSPANOVA;SHLYAKHOVA, 2001;NAKANO et al, 1999;SEGNER;IBE, 1995;VAN AKEN et al, 2008). Adicionalmente, a norma ISO 15.841 também indica a avaliação dos resultados em descarga.…”
Section: Avaliação Dos Resultados Em Descargaunclassified